Developing ‘Islam and Religious Moderation’ Course Based on Kampus Merdeka in Islamic Higher Education - Ahmad Jamin; Heri Mudra (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The focus of the research is the development of the subject